Shirley M. Hufstedler papers - Hufstedler, Shirley M.
Correspondence, memoranda, speeches, policy statements, and other papers relating chiefly to Hufstedler's tenure as U.S. secretary of education in the Jimmy Carter administration, particularly to the Youth Act of 1980 (never enacted) and other legislation, the promotion of various educational programs, and policy issues. Includes a transcript of an interview in which Hufstedler comments on her early life, judicial career, and cabinet appointment. Correspondents include David L. Bazelon, Harry A. Blackmun, Jimmy Carter, Warren Christopher, Clement F. Haynsworth, Joan Mondale, Lewis F. Powell, Betty Rhodes, Kenneth O. Rhodes, Carl T. Rowan, and Cyrus R. Vance.
In part, microfilm edition only
Positive photocopies and microfilm.
Lawyer and jurist, of California; and U.S. secretary of education . Born 1925. Maiden name: Shirley Mount.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bazelon, David L. -- Correspondence; Blackmun, Harry A. -- 1908-1999 -- Correspondence; Carter, Jimmy, -- 1924-; Carter, Jimmy, -- 1924- -- Correspondence; Christopher, Warren -- Correspondence; Haynsworth, Clement F. -- 1912-1989 -- Correspondence; Mondale, Joan -- Correspondence; Powell, Lewis F., -- 1907-1998 -- Correspondence; Rhodes, Betty -- Correspondence; Rhodes, Kenneth O., -- 1912-2005 -- Correspondence; Rowan, Carl T. -- 1925-2000 -- Correspondence; Vance, Cyrus R. -- 1917-2002 -- Correspondence; United States. -- Department of Education; Courts -- California; Education -- United States; Education and state -- United States; Educational law and legislation -- United States; Practice of law -- California; United States -- Social policy; Cabinet officers; Jurists; Lawyers